THE MEDIATING ROLE OF ONLINE PAYMENT IN THE RELATIONSHIP BETWEEN TIKTOK PRODUCT REVIEWS AND PURCHASE DECISIONS ON E-COMMERCE PLATFORMS - Duhita, Amanda Ridha Pradya (Jurnal MBE Manajemen Bisnis, Equilibrium, 2025)
This study aims to examine the effect of product reviews on TikTok on consumer purchase decisions on the Tokopedia e-commerce platform, with online payment as a mediating variable. A quantitative approach was used by distributing a structured questionnaire to 100 purposively selected respondents in Surabaya who actively use TikTok and Tokopedia. Data were analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that product reviews have a positive influence on purchase decisions, both directly and through online payment. Online payment serves as a key factor that links consumer interest with actual purchasing behavior. The credibility of reviews and the ease of digital payment systems significantly strengthen purchasing decisions. These findings imply that e-commerce businesses and MSMEs should integrate social media content strategies with secure and convenient payment systems to increase conversions and enhance consumer experience.